The Meta-Organism Response of the Environmental Generalist Pocillopora damicornis Exposed to Differential Accumulation of Heat Stress - Bergman, Jessica L.; Leggat, William; Ainsworth, Tracy D. (Frontiers in Marine Science, 2021)
Bleaching events in the marine environment are now occurring globally, and the frequency and severity of these events are increasing. Critically, these events can cause the symbiosis between Symbiodiniaceae and their coral hosts to break down, however what is still equivocal is how the microbial community within the coral responds to bleaching. Here we investigate the impact of thermal stress exposure on the meta-organism responses of the generalist scleractinian coral species Pocillopora damicornis. Using mesocosms to recreate warming scenarios previously observed at Heron Island, we show that P. damicornis symbiont densities and photophysiological parameters decline at a similar rate under thermal stress regardless of length of pre-stress period. However, we find that the P. damicornis microbiome remains stable over time regardless of the degree of thermal stress and the accumulation of pre-bleaching thermal stress. Our study therefore suggests that while P. damicornis is physiologically impacted by bleaching temperatures, the microbial community remains unchanged at the taxonomic level identifiable here, throughout bleaching. Given that P. damicornis is an environmental generalist coral species common throughout the Indo-Pacific, understanding the capacity of this coral to withstand bleaching events is imperative. Furthermore, the widespread distribution of environmental generalist coral species as a whole suggests their potential contribution to coral reef structure under future climate conditions and as such the biology, physiology and bleaching responses of these corals needs to be determined.